Mode stresses for the interaction between an inclined crack and a curved crack in plane elasticity - Nik Long N.M.A.; Aridi M.R.; Eshkuvatov Z.K. (Hindawi Publishing Corporation, 2023)
Cracks; Complex variable function method; Curved crack; Hypersingular integral equation; In-plane elasticity; Inclined crack; Mode II; Mode III; Quadrature rules; Integral equations